Sediment sink-source transitions in the middle and lower reaches of the Yangtze River estuary - Yang, Yunping; Zheng, Jinhai; Zhang, Mingjin; Zhu, Lingling (Frontiers in Marine Science, 2023)
Human activities have severely altered the Yangtze River (Changjiang) Estuary's pattern, beach-trough shape, and delta in recent decades. Existing research has studied the sediment “source–sink” relationship between of the Yangtze River mainstream and estuary using gauged suspended sediment data. This method overestimated the decline in the suspended sediment concentration in the estuary, as riverbed scouring or deposition have not filtered out amounts related to sand mining, waterway dredging. The Yangtze Estuary Delta is dominated by scouring, which shows an increasing trend. After the operation of the Three Gorges Reservoir (TGR) operation (2003–2020), the suspended sediment load entering the Yangtze Estuary from of the Yangtze River mainstream decreased by 68% compared with the amount prior to the operation (1960–2002). However, studies have found that there are still large amounts of bottom sand with riverbed load movement characteristics, after the operation of the Three Gorges Project, riverbed souring of the downstream dam increases the deposition recharge degree. The number of sediments in the Yangtze Estuary decreased in 2003–2018 compared with 1981–2002, with an annual decrease of 16.9%. The cumulative deposition of the Yichang–Datong and Datong–Xuliujing reaches from 1981–2002 was 3.13×108 m3 and 1.60×108 m3, respectively, and cumulative scouring from 2002–2018 was 28.52×108 m3 and 16.01×108 m3. This study concluded that even if the suspended sediment load entering the estuary decreased significantly after the operation of the TGR, the riverbed in the middle-lower reaches of the Yangtze River has gradually transformed from the "sink" of sediment deposition to the "source" of sediment supply.